Toward a better understanding of self‐regulation promoting interventions: when performance management and job crafting meet - Demerouti, Evangelia; Roth, Colin; Ebner, Katharina; Soucek, Roman; Moser, Klaus (Human Resource Management, 2024)
Organizations utilize self-regulation promoting interventions to empower employees in managing challenges and resources autonomously. However, there is limited understanding of how these interventions impact employee task performance and innovative behavior, as well as which processes are critical for their effectiveness. Therefore, a field experiment was conducted to examine the effects of two self-regulation promoting interventions—the Productivity Measurement and Enhancement Systems intervention (ProMES), a job crafting intervention, and their combination—on individual employee performance and innovation through selected process variables. We collected data before, during, and after the interventions over 16 weeks among 123 employees across three experimental and one control group. Consistent with predictions, participants of the ProMES intervention reported a higher level of perceived team climate, which consequently contributed to greater individual innovative behavior. Participants in the job crafting intervention exhibited an increase in job crafting behaviors, which consequently increased innovative behavior and task performance. Unexpectedly, the combined intervention yielded negative effects on both innovative behavior and task performance. The findings suggest that while self-regulation promoting interventions increase favorable outcomes through different mechanisms their combination may impair relevant processes and, more generally, overwhelm employees.